ADOPTION AND USE OF ELETRONIC GOVERNMENT WEBSITES IN THE NATIONAL SCIENCE AND TECHNOLOGY AND INNOVATION ENVIRONMENT: A STUDY BASED ON THE UTAUT MODEL - Costa, Érico da Silva (2014)
The relationships between citizens and governments have been complemented by the intensive use of Information Technology and Communication (ICT) for transactional services online. The Brazilian Innovation Portal was developed by the Ministry of Science, Technology and Innovation (MSTI) in partnership with the Center for Strategic Studies and Management (CSSM), Brazilian Association for Industrial Development (BAID) and Instituto Stela to meet demands the National System of Science, Technology and Innovation (NSSTI). Based on Unified Theory of Acceptance and Use of Technology and structural equation modeling technique, the main results of this study showed high predictive significance and magnitude of the Behavioral Intention of Use Portal by the following factors: Expected Performance and Social Influence. Therefore, the social factor is highly influential in the intention to use the technology as well as aspects related to user productivity and the consequent sense utility, plus the ease of interaction and domain tool. Such findings supplement new perspectives in studies in the field of e-Gov, as well as in evaluation of government projects.